SAT0173 Assessment of Left Ventricular Dyssynchrony in Patients with Familial Mediterranean Fever. (10th June 2014) - Ustun, N.; Celik, M.; Kurt, M.; Sen, N.; Akcay, A.B.; Turhanoglu, A.D.
Abstract : Background: Familial Mediterranean fever (FMF) is a disease characterized by recurrent and sustained increased inflammatory activity. Various clinical and subclinical cardiovascular involvements have been reported in FMF patients. However, there is considerable lack of evidence regarding contraction synchrony in FMF. Objectives: We aimed to study the left ventricular contraction synchrony in FMF patients with narrow QRS and normal EF. Methods: Seventy patients with FMF and 35 age- and sex- matched control subjects were included the study. Left ventricular dyssynchrony was investigated by color coded tissue Doppler imaging. Results: In the FMF group, the mean high-sensitive C-reactive protein (hs-CRP) values were significantly higher, compared with the controls (p<0.01). According to the tissue Doppler measurements, E/Em value exhibited statistically significant increase in FMF patient and mean Em value were found to be significantly low (p<0.01). In the control group, two patients had diastolic dysfunction, whereas in the FMF group there were 23 (%46) patients with diastolic dysfunction. LV systolic dyssynchrony parameters including Ts-SD-12, Ts-12, Ts-SD-6, and Ts-6 were found to be higher in FMF group when compared to controls (p<0.01). In addition to that, number of the patients with ventricular dyssynchrony (a Ts-SD-12>34.4 ms) were higher in the FMF group than the control group (34.2±6.9 vs. 24.7±5.8; p<0.01). Ventricular dyssynchrony was detected in all FMF patients with diastolic dysfunction. In the correlation analysis, systolic dyssynchrony parameters were found to be correlated with hs-CRP, E/Em, and Em (p<0.01). Conclusions: We found out that in FMF patients with normal EF and narrow QRS, left ventricular systolic dyssynchrony is an early manifestation of heart involvement and may be coexisted with by diastolic dysfunction. References: Kiris A, Karkucak M, Karaman K, Kiris G, Capkin E, Gokmen F, et al. Patients with ankylosing spondylitis have evidence of left ventricular asynchrony. Echocardiography. 2012 Jul;29(6):661-7. Lachmann HJ, Sengul B, Yavuzsen TU, Booth DR, Booth SE, Bybee A, et al. Clinical and subclinical inflammation in patients with familial Mediterranean fever and in heterozygous carriers of MEFV mutations. Rheumatology (Oxford). 2006 Jun;45(6):746-50. Korkmaz C, Ozdogan H, Kasapcopur O, Yazici H. Acute phase response in familial Mediterranean fever. Ann Rheum Dis. 2002 Jan;61(1):79-81. Tavil Y, Ureten K, Ozturk MA, Sen N, Kaya MG, Cemri M, et al. The detailed assessment of left and right ventricular functions by tissue Doppler imaging in patients with familial Mediterranean fever. Clin Rheumatol. 2008 Feb;27(2):189-94. Baysal T, Peru H, Oran B, Sahin TK, Koksal Y, Karaaslan S. Left ventricular diastolic function evaluated with tissue Doppler imaging in children with familial Mediterranean fever. Clin Rheumatol. 2009 Jan;28(1):23-8. Kalkan GY, Bayram NA, Erten S, Keles T, Durmaz T, Akcay M, et al. Evaluation of left ventricle function by strain imaging in patients with familial Mediterranean fever. Echocardiography. Oct;27(9):1056-60. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1345